Enterprise Architecture pada Layanan Managed Service untuk Kawasan Industri Cilegon - Boy Muhammad Ridwan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Industrial Estate is an area where Industrial activities are concentrated which is equipped with supporting facilities and infrastructure developed and managed by an Industrial Estate Company that already has an Industrial Estate Business Permit. One of the industrial areas with the highest concentration of chemical industry in the country is the Cilegon area, Banten. The city, dubbed the City of Steel, is very attractive as an investment destination for foreign investors. Of course, one of the opportunities with the presence of investment in the industry is managed services. In this paper, we will discuss the opportunities for managed services that are suitable for market needs, which are very good business revenue targets. Various service needs for companies in the industrial area include ERP Implementation with SAP, Internet and Fiber Optic Rental Services, SAP Consulting Services, Managed Services, Infrastructure and Application Maintenance, Application Development and IT Infrastructure Implementation. Seeing the many business opportunities mentioned above, this paper will focus on managed services that have high efficiency values so that they can maximize profits. By using the Enterprise Architecture design for managed services, it will be possible to see what kind of business model suits the needs of customers in the Cilegon industrial area. The business model will be described in the Business Model Canvas and use the Archimate Core Framework elements to visualize the Enterprise Architecture system that is integrated between business elements, data and applications, and technology. In this study using Enterprise Architecture for service management services which is a method used in implementing strategically managing services in the field of information technology in a company from various aspects of the system to increase company revenue.